Detection of antigens with affinity for host cell membrane polypeptides in culture supernatants of Trypanosoma cruzi. - Davis, C D (1990)
Parasite antigens which bind to host cell molecules of approximately 32 and 34 kilodaltons (kDa) were identified in supernatant fluids obtained from axenic cultures of Trypanosoma cruzi. These parasite components were first detected in culture supernatants obtained after 2 weeks in culture. Immunoblot analysis of culture supernatants exhibiting binding activity revealed the presence of several parasite antigens ranging in molecular mass from approximately 26 to 290 kDa. Gel filtration (Sephacryl S-300) analysis of culture supernatants revealed four major peaks, but only the highest-molecular-mass peak (containing several parasite antigens ranging from 27 to 250 kDa) possessed binding activity for the host cell molecules.